Characterization of CD3+ T Lymphocytes in Human Coronary Thrombi with ST-segment Elevation Myocardial Infarction - Gu, Muyang; Xia, Ni; Zhang, Si; Zhu, Xinyu; Liu, Meilin; Lu, Yuzhi; Li, Nana; Yang, Haoyi; Tang, Tingting; Nie, Shaofang; Li, Jingyong; Yang, Fen; Jiao, Jiao; Lv, Bingjie; Wang, Weimin; Hu, Desheng; Hu, Jiong; Liu, Huirong; Chen, Chen; Cheng, Xiang (Thrombosis and Haemostasis, 2024)
Background The occurrence and development of ST-segment elevation myocardial infarction (STEMI) are accompanied by coronary atherothrombosis and occlusion, and immune responses play prominent roles in their pathogeneses. However, the causes of atherothrombosis remain elusive, and a comprehensive study of T cell-mediated immune responses in coronary thrombi from STEMI patients is lacking.Objectives The aim of this study was to determine the heterogeneity and clonality of CD3+ T lymphocytes in STEMI patients at the single-cell level.Methods Paired single-cell RNA and T cell receptor (TCR) sequencing was performed on CD3+ T lymphocytes in the coronary thrombi and peripheral blood of STEMI patients, as well as the blood from control subjects without coronary artery disease (CAD).Results Compared with those in the peripheral blood of STEMI patients, the activation, cytotoxicity, proinflammatory, and prothrombotic characteristics of CD3+ T lymphocytes in coronary thrombi were decreased, and the clonality of CD3+ T cells was increased. Compared with those from non-CAD controls, T lymphocytes from STEMI patients exhibited an upregulation of genes related to recent TCR engagement, suggesting antigen-specific stimulation in STEMI. Antigen specificity prediction using an algorithm indicated the probability of T cells from different patients binding to similar antigens for clonal expansion during STEMI.Conclusion This study provides a basis for exploring the cellular heterogeneity of CD3+ T lymphocytes in the coronary thrombi and peripheral blood of STEMI patients. Identifying the precise adaptive immune mechanisms driving atherothrombosis may lead to innovative therapies that selectively target the aberrant immune response, resulting in more effective treatments for STEMI.
Keywords: STEMI; T lymphocyte; coronary thrombosis; platelets; T cell receptors